Classification of halal product by using decision tree / Nor Shazwani Ismail - Nor Shazwani, Ismail (2013)
In "Ice Cream," (2009), there were many varieties of ice cream's flavours such as chocolate, strawberries, vanilla and coffee. However, be aware since some of the ice cream's ingredients contains alcohol and unknown resources. Currently, with the growth of ice cream production, many manufacturers want to produce ice cream-based product. This research implementation is to classify the halal status of ice cream using decision tree. Several attributes are used in order to classify whether the ice cream is halal, haram or doubtful. This research also implements an experiment for three methods to find out which method to be used among J48 Decision Tree, Na'ive-Bayes Tree and Logistic Model Tree. The best accuracy result will be implemented in this prototype. Most of Halal system detection that was available is created only for their product inside the country. Besides, many researchers use decision tree to classify data but only a few of them focus on Halal product and because of that the decision tree was implemented in this research.